A phase I trial of immunostimulatory CpG 7909 oligodeoxynucleotide and 90yttrium ibritumomab tiuxetan radioimmunotherapy for relapsed B‐cell non‐Hodgkin lymphoma. Issue 7 (12th June 2013) - Witzig, Thomas E.; Wiseman, Gregory A.; Maurer, Matthew J.; Habermann, Thomas M.; Micallef, Ivana N.M.; Nowakowski, Grzegorz S.; Ansell, Stephen M.; Colgan, Joseph P.; Inwards, David J.; Porrata, Luis F.; Link, Brian K.; Zent, Clive S.; et al.
<x xml:space="preserve">Abstract</x> Radioimmunotherapy (RIT) for relapsed indolent non‐Hodgkin lymphoma produces overall response rates (ORR) of 80% with mostly partial remissions. Synthetic CpG oligonucleotides change the phenotype of malignant B‐cells, are immunostimulatory, and can produce responses when injected intratumorally and combined with conventional radiation. In this phase I trial, we tested systemic administration of both CpG and RIT. Eligible patients had biopsy‐proven previously treated CD20+ B‐cell NHL and met criteria for RIT. Patients received rituximab 250 mg/m2 days 1, 8, and 15; 111In‐ibritumomab tiuxetan days 1, 8; CpG 7909 days 6, 13, 20, 27; and 0.4 mCi/kg of 90Y‐ibritumomab tiuxetan day 15. The doses of CpG 7909 tested were 0.08, 0.16, 0.32 (six patients each) and 0.48 mg/kg (12 patients) IV over 2 hr without dose limiting toxicity. The ORR was 93% (28/30) with 63% (19/30) complete remission (CR); median progression free survival of 42.7 months (95% CI 18‐NR); and median duration of response (DR) of 35 months (4.6–76+). Correlative studies demonstrated a decrease in IL10 and TNFα, and an increase in IL1β, in response to therapy. CpG 7909 at a dose of 0.48 mg/kg is safe with standard RIT and produces a high CR rate and long DR; these results warrant confirmation. Am. J. Hematol. 88:589–593, 2013. © 2013 Wiley Periodicals, Inc.